The Effect of Relationship-Oriented Leadership Behavior,Promotion of Position and Work Environment on the Performance of Civil Servants at the Agricultural Quarantine Center in Surabaya - Khoirun Nisa; Wahyu Eko Pujianto (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This study aims to describe and analyze the influence of relationship-oriented leadership, promotion, and work environment on the performance of civil servants at the Agricultural Quarantine Center in Surabaya.Design/Methodology/Approach – The type of research used is explanatory research. The number of samples in this study was 100 employees of the Surabaya Agricultural Quarantine Center. The data analysis used is the analysis of the outer model, inner model, and hypothesis testing using SmartPLS 4.0.Findings - Research results show that; relationship-oriented leadership behavior has a significant effect on employee performance; promotion has a partially significant and positive effect on employee performance; the work environment has a partial effect on employee performance; and relationship-oriented leadership behavior, promotion, and work environment have a positive and significant effect simultaneously on employee performance.leadership